Women Empowerment on Waste Management in Sub-District of Dau, Malang Regency - Wike Wike; Harsuko Riniwati; Endah Setyowati (Proceedings of AICS - Social Sciences, 2017)
This paper aims to explore women empowerment in waste management in Sub-District Dau, Malang. This research used questionnaire to obtain data and then the data have been analyzed by using MDSs in order to assess the index and sustainability on women empowerment through a 5 dimensions. The results of analysis of the dimensions are Control (26,71), Implementation (39,36), Monev or Monitoring and Evaluation (32,63), Development Utilization (37,44), Level of Participation (33,45). The index shows that it is lower level. Therefore, if it is to maintain or improve the sustainability status of women empowerment